WANITA KARIR DALAM PERSPEKTIF HUKUM ISLAM: (Tinjauan Keluarga Sakinah Dosen STAI Jamiatut Tarbiyah Lhoksukon Aceh Utara) - Cut Ali, Isnu; Nasir, Muhammad (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2025)
The background of the study examines how career women are considered to be moving and towards gender equality with men, but career women are considered a step backwards in maintaining the image of Eastern customs. Research objectives: 1) to know the efforts of career women in realizing a harmonious family. 2) find out the position of career women in a harmonious family. 3) find out the existence of career women in the analysis of Islamic law. This research was conducted on female lecturers at STAI Jamiatut Tarbiyah, Lhoksukon North Aceh Campus using a qualitative descriptive approach, which seeks to describe some data obtained from the field, both through interviews, observations, and documentation. Then it is continued with the data analysis process. The results of this study show that: 1) The efforts of women who have careers as lecturers at STAI Jamiatut Tarbiyah Lhoksukon Aceh Utara in realizing a harmonious family include: a) quality time, b) maintaining good communication, c) open attitude, d) mutual understanding, e) time management, f) husband's support for his wife for a career, g) maintaining family integrity; 2) The position of the career woman in the concept of a harmonious family is still below the position of her husband so that she must remain obedient and obedient to her husband; 3) In the analysis of Islamic law, there is no distinction between the right of men and women to work, both are given the opportunity and freedom to struggle and earn their own livelihood on this earth.